Research progress in AIE-based crystalline porous materials for biomedical applications. (July 2022) - Zeng, Jin-Yue; Wang, Xiao-Shuang; Sun, Yun-Xia; Zhang, Xian-Zheng
Abstract: Crystalline porous materials (CPMs) not only present the precise integration of molecular building blocks into extensible structures with periodic frameworks and regular pores, but also provide limited molecular spaces for the interactions of guest molecules, electrons and photons. Incorporating aggregation-induced emission (AIE)-based units into crystalline porous frameworks can result in unique luminescent properties. AIE-based CPMs have widely tunable composition, high luminescent efficiency and good photo-stability, which make them useful for biomedical applications involving bio-sensing, bio-imaging and imaging-guided therapies. This review focused on structure design and luminescent property modulation of AIE-based CPMs with highlights on their applications in biomedical fields. The prospect and challenges in the development of AIE-based CPMs from chemistry, materials to biomedical applications were also discussed.